Analisis efektivitas desain komunikasi visual sebagai media promosi menggunakan customer response index - Uyuunul Mauidzoh; Yuliani Indrianingsih; Astika Ayuningtyas (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2022)
Salam Village is one of the villages in Patuk District, Gunungkidul Regency. Geographical location and natural resources are assets for Salam Village as a tourist spot. There are many interesting tourist objects, which are not well known by the public. In general, tourist attractions in Gunungkidul are widely known by the public. The problems raised in this study are 1) How to design attractive and communicative promotional materials so that Salam village becomes a tourist spot that is known by the public 2) How to create visual communication ideas that can support the promotion of Salam Village, Patuk Gunungkidul District 3) How is the effectiveness of visual communication design as a medium to promote Salam Village, Patuk Gunungkidul District. While the objectives are 1) Designing attractive and communicative promotional design materials, so that Salam village becomes a tourist spot that is known by the public 2) Creating visual communication design ideas that can support the promotion of Salam Village so that it becomes known by the wider community 3) Knowing the effectiveness of visual communication media in promoting tourism objects in Salam village, Patuk Gunungkidul sub-district. The method used in this research is to create a visual communication design for tourism objects in Salam Village, Patuk District, Gunungkidul Regency. To assess the effectiveness of the visual communication design using the Customer Response Index (CRI) method. Using audio-visual media, the tourism potential of Purboselo Nawing can be clearer and get the attention of the public. In designing a promotional video, all the needs of stakeholders, especially Purboselo Nawing, can be packaged into one medium, namely an audio visual media. In the end, it is hoped that this video will help Pokdarwis which manages Purboselo Nawing in conveying the message that the wider community wants to capture, as part of the promotion of tourist destinations. The CRI calculation in this study implements the AISAS concept which consists of five indicators, namely attention, interest, search, action, and share. The results of the calculation of CRI with the AISAS concept obtained in this study are as follows: CRI AISAS of 18.01%, CRI of AIAS of 18.76%, CRI of AISS of 40.82%, and CRI of AIS of 43.52%. Consumer response to Purboselonawing advertisements/promotions on Instagram and YouTube accounts is relatively good. This can be seen at the attention stage the value is 54.67%. At the interest stage, respondents are very interested in advertising/promotions purboselonawing with a value of 93%. At the search stage, the results are very good, which is 96%. At the action stage, it is also quite good with a value of 44.12%. Meanwhile, the willingness to share advertisements is quite good with a value of 83.64%.